Fresno County Bar Association Annual Bar Banquet Held at Elks Lodge - Watkins, Howard::::::::: (1981)
John McGregor standing at head table; others Hal Bolen II, Jim Gregory, John "Nip" Gallagher, Stephen Kane, and Harold Lai